A Tracking System Supporting Large-Scale Users Based on GPS and G-Sensor. (27th May 2015) - Zeng, Jun; Li, Minbo; Cai, Yuanfeng
As the need for tracking objects in our daily life is increasing, how to take advantage of widely used technologies and devices to meet everyone's need is becoming a burning issue. To achieve this aim, a tracking system supporting large-scale users based on GPS and G-sensors (TSSLSU) is designed to track items by obtaining various pieces information of the item's states and analyzing various conditions. In this system, a microprocessor with Global Positioning System (GPS) modules embedded in target sends data in real-time through General Packet Radio Service (GPRS) and Global System for Mobile Communication (GSM), and an inner G-sensor can fetch real-time state information, such as acceleration and vibration signals. The system designed a message protocol to encapsulate and send these data to servers and also adopted distributed architecture, including backend server cluster, cache queue cluster, database cluster, and web server cluster. This specific architecture provides a better performance when large-scale users visit concurrently. In particular, there are alarm mechanisms to inform the user of any illegal cases through smart phone application and power-saving mechanism for embedded terminal by changing the frequency of sending messages. At any time, user can locate it and query the carrier's previous path by web page or phone application.